1992
DOI: 10.1037/0735-7044.106.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Associative retuning in the thalamic source of input to the amygdala and auditory cortex: Receptive field plasticity in the medial division of the medial geniculate body.

Abstract: The medial division of the medial geniculate body (MGm) projects to the lateral amygdala and the upper layer of auditory cortex and develops physiological plasticity rapidly during classical conditioning. The effects of learning on frequency receptive fields (RFs) in the MGm of the guinea pig have been determined. Classical conditioning (tone-footshock), as indexed by rapid development of conditioned bradycardia, produced conditioned stimulus (CS)-frequency specific RF plasticity: increased response at the CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 69 publications
12
140
0
1
Order By: Relevance
“…NIH-PA Author Manuscript NIH-PA Author Manuscript because MGm RFs are much more complex, multipeaked and broadly tuned than those of auditory cortical cells [55][56][57] . Therefore, long-term, specific plasticity in A1 is not merely a reflection of plasticity in the subcortical auditory system but probably reflects processes in the cortex.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…NIH-PA Author Manuscript NIH-PA Author Manuscript because MGm RFs are much more complex, multipeaked and broadly tuned than those of auditory cortical cells [55][56][57] . Therefore, long-term, specific plasticity in A1 is not merely a reflection of plasticity in the subcortical auditory system but probably reflects processes in the cortex.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The Suga model ignores the MGm, its intrinsic associative plasticity and its influences on both A1 and the lateral amygdala (LA), but the following findings directly implicate the MGm: acoustic and nociceptive information converge directly in the MGm 58,59 ; associative learning is accompanied by the development of plasticity in the MGm [60][61][62][63][64][65][66] , which is longlasting 63 and is evident as CS-specific RF plasticity after conditioning 56,67 ; the MGm holds an associative memory trace after CS offset during conditioning 68 ; analogues of learning show that stimulation of the MGm induces long-term potentiation in A1 (REF. 69) and tone paired with stimulation of the MGm induces heterosynaptic long-term potentiation in A1 (REF.…”
Section: Loci Of Plasticitymentioning
confidence: 99%
“…An involvement of the medial geniculate (MG) nucleus in aversively motivated learning is indicated by the observation of TIA in the medial division of the MG nucleus (MGm) (Olds et al., 1972;Gabriel et al, 1975;Gabriel et al, 1976;Ryugo and Weinberger, 1978;Birt and Olds, 1981;Weinberger, 1982;Edeline, 1990;Edeline and Weinberger, 1992;McEchron et al, 1995), and by impaired conditioning in animals with MG lesions (Iwata et al, 1986;Jarrell et al, 1986; LeDoux et al, 1986a,b;McCabe et al, 1993). Amygdalar and MG neurons are involved in aversively motivated instrumental conditioning processes, as well as in classical aversive conditioning.…”
Section: Abstract: Limbic Thalamus; Cingulate Cortex; Amygdala; Learmentioning
confidence: 99%
“…A central role of amygdalar neurons is indicated by findings that amygdala lesions impair the acquisition of conditioned immobility (LeDoux et al, 1988; Fanselow and K im, 1994;LeDoux, 1995), autonomic responding (Blanchard and Blanchard, 1972;Spevack et al, 1975;Kapp et al, 1979;Gentile et al, 1986;Iwata et al, 1986;Helmstetter, 1992) and fear-potentiated startle behavior (Davis, 1986(Davis, , 1992Hitchcock and Davis, 1987;Sananes and Davis, 1992). Also, amygdalar neurons exhibit associative, training-induced activity (TIA) during Pavlovian conditioning (Umemoto and Olds, 1975;Applegate et al, 1982;Pascoe and Kapp, 1985;Nishijo et al, 1988; Muramoto et al, 1993;McEchron et al, 1995;Quirk et al, 1995).An involvement of the medial geniculate (MG) nucleus in aversively motivated learning is indicated by the observation of TIA in the medial division of the MG nucleus (MGm) (Olds et al., 1972;Gabriel et al, 1975;Gabriel et al, 1976;Ryugo and Weinberger, 1978;Birt and Olds, 1981;Weinberger, 1982;Edeline, 1990;Edeline and Weinberger, 1992;McEchron et al, 1995), and by impaired conditioning in animals with MG lesions (Iwata et al, 1986;Jarrell et al, 1986; LeDoux et al, 1986a,b;McCabe et al, 1993). Amygdalar and MG neurons are involved in aversively motivated instrumental conditioning processes, as well as in classical aversive conditioning.…”
mentioning
confidence: 99%
“…Some studies have indicated the existence of a double sub-cortical pathway for auditory processing, only one of them showing neuronal plasticity. Specifically, the ventral division of the medial geniculate body (MGBv) does not show plasticity, while changes similar to those observed at the cortical level have been detected in the medial division of the MGB, which might thus be considered functionally as part of the neuronal system for learning (Edeline & Weinberger, 1992).…”
Section: Fear Conditioning Induces Plastic Changes In Neuronal Responmentioning
confidence: 99%